Prevalence of hyperandrogenism in Iraqi women with polycystic ovary syndrome - Alsaadi, Yasmin L.; Mohamad , Ban Jasim (Iraqi Journal of Science, 2019)
Polycystic ovary syndrome (PCOS) is a mainly common endocrine disorder. Hyperandrogenism is the major standard in the diagnosisof PCOS development.Eighty women diagnosed with PCOS and twenty healthy women(aged 20-40 years)were enrolled in this study which was conducted at the infertility clinic of Kamal AL-Samaraay Hospital/ Baghdad. The diagnosis of PCOS was made according to the Rotterdam criteria. Body mass index (BMI, Kg/m2)was calculated by a specific formula. History of menstrual irregularity, hirsutism, acne, and alopecia was taken. Hormone levels in serum, namely luteinizing hormone (LH), follicle stimulating hormone (FSH), and testosterone were measured in all patients and control subjects.There was a statistically significant difference (P <0.05) in the BMI between the PCOS and control women.Also, the prevalence of overweight and obesity was much higher in PCOS women than in their matching control. The serum levels of LH, FSH, and testosterone were significantly different (P <0.05) in PCOS as compared to healthy women. Clinical hyperandrogenism (hirsutism and alopecia) were present in most of PCOS women, while acne wasa less useful clinical sign of hyperandrogenism.Inaddition, the prevalence of hirsutism and alopecia was increased in obese when compared with overweight and lean PCOS women.